Bio-Functional Activities of Tuscan Bee Pollen - Elisa Chelucci; Carolina Chiellini; Andrea Cavallero; Morena Gabriele (MDPI AG, 2023)
Bee pollen represents one of the most complete natural foods playing an important role in the diet for its health qualities and therapeutic properties. This work aimed to characterize a Tuscan bee pollen by evaluating its phytochemical profile and the in vitro and ex vivo antioxidant activities. The isolation and taxonomic and functional characterization of yeasts in the sample has been also conducted. Finally, the pollen anti-inflammatory potential has been assessed on a TNFα-inflamed human colorectal adenocarcinoma cell line (HT-29). Our results highlighted a good phytochemical composition in terms of polyphenols, flavonoids, flavonols, monomeric anthocyanins, and carotenoids. In addition, we detected good antioxidant activity and radical scavenging capacity by in vitro and ex vivo assays, as well as good antioxidant activity by isolated yeasts. Data showed no cytotoxic effects of bee pollen extracts, with average viability values >80% at each tested dose. Moreover, TNFα treatment did not affect HT-29 viability while upregulating IL-8, COX-2, and ICAM-1 gene expression, otherwise reduced by both doses of bee pollen. In conclusion, our sample represents an interesting functional food and a potential probiotic product, having high phytochemical compound levels and good antioxidant activities, as well as anti-inflammatory effects on the TNFα-inflamed HT-29 cell line.